2021
DOI: 10.1021/acs.langmuir.1c00245
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Mounted Metal–Organic Frameworks: Past, Present, and Future Perspectives

Abstract: Metal–organic frameworks (MOFs) are an emerging class of porous materials composed of organic linkers and metal centers/clusters. The integration of MOFs onto the solid surface as thin films/coatings has spurred great interest, thanks to leveraging control over their morphology (such as size- and shape-regulated crystals) and orientation, flexible processability, and easy recyclability. These aspects, in synergy, promise a wide range of applications, including but not limited to gas/liquid separations, chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 140 publications
0
27
0
4
Order By: Relevance
“…[9] Für das Ziel der elektrochemischen Anwendungen ist die Integration von PP-MOFs auf festen Oberflächen als Film eine Voraussetzung, die wir hier erreichen. [10] Neulich wurde Mn-PCN-222, modifiziert mit Polyglutaminsäure, bereits als elektrochemischer H 2 O 2 -Sensor eingesetzt. [9b] Die Vorteile von Mn-PCN-222 beruhen jedoch auf der rationalen Kombination von Metalloporphyrin-Redoxstellen mit Porosität, die jeweils einen einfachen Elektronenund Analytentransport ermçglichen.…”
Section: Einführungunclassified
“…[9] Für das Ziel der elektrochemischen Anwendungen ist die Integration von PP-MOFs auf festen Oberflächen als Film eine Voraussetzung, die wir hier erreichen. [10] Neulich wurde Mn-PCN-222, modifiziert mit Polyglutaminsäure, bereits als elektrochemischer H 2 O 2 -Sensor eingesetzt. [9b] Die Vorteile von Mn-PCN-222 beruhen jedoch auf der rationalen Kombination von Metalloporphyrin-Redoxstellen mit Porosität, die jeweils einen einfachen Elektronenund Analytentransport ermçglichen.…”
Section: Einführungunclassified
“…The concept of functional guests confined in MOF films (often referred to as guest@MOF films) is particularly attractive as it expands the possible applications beyond traditional fields of high‐surface‐area materials. It has been shown that the electrical and optical properties of orientation‐controlled guest@MOF films often strongly depend on the orientation of the confined guest [7–12] . The function of the material can be further tuned by the degree of pore filling, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…via adsorption of self-assembled monolayers, SAMs) have exhibited a high degree of orientation, tunable thickness, and high structural quality often exceeding that of bulk MOF materials. [54][55][56] Although the application of the lbl scheme to be realized highly oriented γCD-MOF appears to be straightforward, no successful realization has been reported so far. A first challenge in this context is the fact that so far a successful application of the lbl method using aqueous conditions has not been reported.…”
Section: Introductionmentioning
confidence: 99%